P5-S7.08 Assessment of chlamydia testing coverage using HEDIS data: USA, 2009. (10th July 2011) - Tao, G; Hoover, K; Romaguera, R; Kent, C
Abstract : Background: In the USA, chlamydia screening of all sexually active women aged ≤25 years is recommended, but screening rates are low. The Healthcare Effectiveness Data and Information Set (HEDIS) performance measure has tracked the time trend in screening since 2000. It has been found that among sexually active women aged 15–25 years, chlamydia testing rates increased from 25.3% to 41.6% during 2000–2007. While rates have increased, they remain suboptimal, and it is unknown whether testing rates differ significantly between 2007 and 2009 or by the type of health plan. Methods: The 2009 HEDIS chlamydia testing dataset was analysed to estimate the annual coverage among sexually active women aged 15–25 years who were enrolled in commercial health plans. Sexually active women were defined as those who had a claim or visit for pregnancy, contraception, cervical cancer screening, or STD diagnosis, screening, or treatment. A woman was counted as having a test if she had a claim or healthcare visit for any chlamydia test. Health plan types included in the HEDIS data are health maintenance organisations (HMOs), preferred provider organisation (PPO), point of service (POS), and any combination of HMO, PPO, and POS. Results: Of 2.4 million sexually active women, 54.5% were enrolled in PPOs, 28.7% in combined HMO/POSs, 13.8% in HMOs, 2.7% in combined HMO/POS/PPOs, and 0.3% in POSs. The overall annual chlamydia testing rate was 44.2% and significantly differed by plan type: 56.1% in HMOs, 45.7% in combined HMO/POSs, 44.6% in POSs, 41.2 in combined HMO/POS/PPOs, and 40.5% in PPOs. Conclusions: The annual chlamydia testing rate continued to increase between 2007 and 2009 (41.6% to 44.2%). However, the testing rate remains suboptimal, suggesting that additional interventions are needed to further increase testing rates. The highest testing rates were found in HMOs, healthcare settings that have interventions in place to promote provision of recommended healthcare services. The 2010 Affordable Care Act requires insurance plans cover preventive services such as chlamydia screening without patient cost sharing, and has the potential to increase chlamydia screening coverage throughout the US healthcare system. In light of these changes, it is important to continue to monitor chlamydia testing practices and to overcome barriers to testing.